A retrospective analysis comparing mandibular fibula reconstruction by transoral versus submandibular approach - XU Fan, MIAO Dongqing, WANG Yuli, BIAN Yifeng, XIAO Na, DU Yifei, DING Xu (Kouqiang yixue)
Objective To compare the clinical and functional differences between transoral and submandibular approach in mandibular segmental resection and reconstruction with free fibula flaps (FFFs). Methods Patients who underwent mandibular segmental resection and FFFs reconstruction in the Department of Oral and Maxillofacial Surgery of the Affiliated Stomatological Hospital of Nanjing Medical University from January 2015 to March 2023 were retrospectively analyzed. All cases were divided into transoral approach and submandibular approach groups. Clinical characteristics of the patients were recorded including age, gender, follow-up time, pathological diagnosis, body mass index (BMI), American Society of Anesthesiologists (ASA) classification, James Brown classification of mandibular defect and number of fibular segments. The perioperative indexes, such as average operation time, average bleeding volume, average blood transfusion volume, average drainage volume, average hospitalization time and postoperative complications such as malocclusion, fistula, infection, flap failure, and restriction of mouth opening were compared between the two groups. The University of Washington Quality of Life Questionnaire was used to investigate the appearance, function of swallow and speech more than 6-month postoperatively. Results The average intraoperative bleeding and postoperative drainage were significantly lower in the transoral approach group than in the submandibular approach group (P=0.013 9, P=0.001 9). The appearance score was significantly higher in the transoral approach group than in the submandibular approach group(83.52±12.37) vs. (67.19±13.64)(P<0.000 1). The differences between the two groups in other variables were not statistically significant. Conclusion Cases of transoral approach had significantly better aesthetic outcomes compared with those of submandibular approach.